(untitled) (Al-Academy, 2025)
Design is plastic innovation, as it is the complete process of planning something and creating it in a way that is not only satisfactory from a functional standpoint, but also brings pleasure to the soul, and this satisfies the human need utilitarianly and aesthetically at the same time. Embroidery is one of the beautiful decorative arts that people use to decorate their clothes. It derives its decorative unity from the surrounding environment, using threads of various types, as well as beads, beads, and other materials that he can shape or add to the embroidered pieces to make them more beautiful. Complements are the magical details of fashion that can change the overall feeling of an individual’s external appearance. They are the addition of a secondary or auxiliary thing that adds a touch of beauty to the outfit, and it can be dispensed with or changed to the outfit. The research aims to: 1- Study of metal materials used in traditional embroidery. 2- Creating decorative designs inspired by traditional embroidery motifs suitable for evening bags. 3- Finding a relationship between authenticity and modernity in borrowing from traditional decorations and designing evening bags. 4- Implementing evening bags embroidered with metals by combining traditional decorations and the art of embroidery with metals. Research recommendations: 1- Collecting and documenting the locations of traditional mineral raw materials on an electronic website for easy access to them and identification of their forms. 2- Directing designers to introduce traditional decorative designs and materials to preserve the traditional heritage. 3- Paying attention to embroidery with metal materials and introducing it more widely into the hand embroidery curricula in the Fashion Department. 4- A comprehensive collection of traditional jewelry in a museum explaining their names, shapes, and the areas in which they are used.